Precise local quasigeoid modelling using GNSS/levelling height anomalies and gravity data. Issue 370 (2nd January 2020) - Trojanowicz, Marek; Osada, Edward; Karsznia, Krzysztof
Abstract : This study compares four approaches of local quasigeoid modelling using GNSS/levelling height anomalies. The first two approaches utilise only a dense network of points with known GNSS/levelling height anomalies and the EGM2008 model. They are based on the interpolation of residual values of height anomalies by applying the least squares collocation ( LSC ) and the thin plate spline ( TPS ). The next two approaches use additional data in the form of surface gravity data and the digital elevation model. One of these approaches is based on the classical Molodensky method combined with LSC . The other approach utilises the method of geophysical gravity data inversion ( GGI ). During the research, the authors used a local network of points with precisely defined GNSS/levelling height anomalies located in South-Western Poland. They obtained comparable results for all tested approaches at the maximum analysed density of GNSS/levelling points (about 1 p o i n t 30 k m 2 ). The differences between the modelling results became apparent only with an increase in the distance between the GNSS/levelling data points and the reduced accuracy of the used global geopotential model.